(untitled) (Castilla. Estudios de Literatura, 2017)
The relationship between autobiography and fiction, as well as the phenomenon of the double, are one of the most popular subjects among the investigators of the works of Roberto Bolaño. Many critics intend to “open” his texts with a “factual key” and discover his truth, describe his way of mixing reality with fantasy. In other words, one of the central problems in Roberto Bolaño’s ouvre is the phnomenon of the autofiction. Instead of participating in the terminological discussions surrounding the subject, in this essay I propose an approach to the different sides of Bolaño through a juxtaposition of three ideas: the dialogism of Mikhail Bakhtin, the “paralactic mode” of Hal Foster and, specifically, the “sylleptic subject” described by a Polish scholar, Ryszard Nycz. These theoretical devices facilitate the description of the process in which Bolaño effectuates the declination of his own identity. The essay consists of a metaphor drawned form the texts of Jorge Luis Boges, a response to other critical readings of Bolaño’s autofiction and an analysis of the literary investigations described by the chilean author. It is concluded by an approach to the “savagery”, Bolaño’s intrinsic condition which reveals itself in the labyrinthic paradigm of his “I”.